The spatiotemporal dynamics of neural activity in the neocortex during waking and sleep in mice - Cui, N (2017)
Sleep is a non-homogenous physiological and behavioural state, which is regulated at many distinct levels, some of which are the focus of this project. The first objective of this project was to investigate cortical EEG dynamics at vigilance state transitions. The experiments have been carried out in adult male C57BL/6 mice, implanted with EEG screws and electromyography (EMG) wires. The main novel finding was that following REM sleep episodes, cortical activity during the initial NREM sleep was desynchronised as compared to NREM sleep episodes following waking. This was manifested in reduced number and amplitude of EEG slow waves and increased incidence of isolated slow waves. The second objective was to investigate how spatiotemporal dynamics of cortical activity during waking and sleep is affected by ongoing behaviour and preceding experience. In these experiments, animals, implanted with EEG electrodes and micro-wire arrays for recording neuronal activity, were recorded during running on a wheel and during subsequent sleep. The result revealed that voluntary wheel running in free-moving mice is associated with a substantial reduction in firing rates among large subpopulation of cortical neurons. The third objective was to address circuit mechanisms of specific brain oscillations in sleep and waking, and their relevance for normal behaviour and disease. Experiments have been carried out in Blind-drunk mice (point mutation in Snap-25 gene), which are a newly established mouse model relevant for schizophrenia. The results confirmed previous findings of a circadian phenotype in Blind-drunk mice, and for the first time characterised their sleep electrophysiology. In conclusion, this work provides novel insights into the effects of preceding behaviour, state and specific waking experience on spatiotemporal dynamics of cortical activity during sleep. Understanding spatio-temporal dynamics of brain activity during sleep is essential for elucidating the mechanisms of sleep regulation and the role of sleep in health and pathology.